Homeodomain‐interacting protein kinase 2 suppresses proliferation and aerobic glycolysis via ERK/cMyc axis in pancreatic cancer. (1st April 2019) - Qin, Yi; Hu, Qiangsheng; Ji, Shunrong; Xu, Jin; Dai, Weixing; Liu, Wensheng; Xu, Wenyan; Sun, Qiqing; Zhang, Zheng; Ni, Quanxing; Yu, Xianjun; Zhang, Bo; et al.
Abstract: Objectives: To investigate the roles of the homeodomain‐interacting protein kinase (HIPK) family of proteins in pancreatic cancer prognosis and the possible molecular mechanism. Materials and Methods: The expression of HIPK family genes and their roles in pancreatic cancer prognosis were analysed by using The Cancer Genome Atlas (TCGA). The roles of HIPK2 in pancreatic cancer proliferation and glycolysis were tested by overexpression of HIPK2 in pancreatic cancer cells, followed by cell proliferation assay, glucose uptake analysis and Seahorse extracellular flux analysis. The mechanism of action of HIPK2 in pancreatic cancer proliferation and glycolysis was explored by examining its effect on the ERK/cMyc axis. Results: Decreased HIPK2 expression indicated worse prognosis of pancreatic cancer. Overexpression of HIPK2 in pancreatic cancer cells decreased cell proliferation and attenuated aerobic glycolysis, which sustained proliferation of cancer cells. HIPK2 decreased cMyc protein levels and expression of cMyc‐targeted glycolytic genes. cMyc was a mediator that regulated HIPK2‐induced decrease in aerobic glycolysis. HIPK2 regulated cMyc protein stability via ERK activation, which phosphorylated and controlled cMyc protein stability. Conclusions: HIPK2 suppressed proliferation of pancreatic cancer in part through inhibiting the ERK/cMyc axis and related aerobic glycolysis.